Post a New Question

Calculus 1

posted by on .

Find the derivative of y with respect to x. y=(x^6/6)(lnx)-(x^6/36)

So far this is what I've gotten:

y=(x^6/6)(lnx)-(x^6/36)
y=(1/6)x^6(lnx)-(1/36)x^6
y'=(1/6)x^5(1/x)+lnx(x^5)-(1/6)x^5

What do I do now?

  • Calculus 1 - ,

    You forgot various parts.

    If y = uv, y' = u'v + uv'
    If y = u^n, y' = nu^(n-1) u'

    So,

    y' = [1/6 * 6x^5 * lnx] + [1/6 x^6 * 1/x] - 1/36 * 6x^5

    or, you can factor stuff out first:

    y = 1/6 x^6 (lnx - 1/6)
    y' = [1/6 * 6x^5](lnx - 1/6) + 1/6 x^6 * (1/x)

    Either way you can massage things till you get

    x^5 lnx

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question